Rationalizing public sector employment in the MENA Region - Bulmer, Elizabeth Ruppert (Washington,D.C World Bank, 2000)
The report focuses on the challenging labor market environment in the Middle East and North Africa region, characterized by overstaffing in the public sector, and exacerbated by a distorted underlying incentive framework. This has led to segmentation along public/private lines, and between foreign, and national labor in the Gulf countries. Various policy measures can be used to reduce public sector employment, thus the report provides useful lessons, and international experience for policymakers, especially with respect to designing effective severance, or unemployment benefits, creating consensus on the need to retrench, and minimizing adverse selection effects. The report also addresses the need to ensure a more efficient labor reallocation toward the private sector, which will, require, however, complementary measures to improve the underlying incentive structure, including constraints in economic policy
I. Overview of employment challenges and policy objectives in MENA -- II. Magnitude of the problem -- Policy instruments to reduce public sector employment -- IV. Complementary measures to achieve policy objectives -- V. Conclusions -- References
Summaries in Arabic and French also
Includes bibliographical references (p. 25-27)
Keywords: Labour market; LABOUR MARKET; PUBLIC SECTOR; EMPLOYMENT; MIDDLE EAST; NORTH AFRICA; MENA